Chronic constipation with associated comorbid conditions: a physician survey on clinical perspectives on its diagnosis and management - Kumar, Rakesh; Ramakrishnan, S. R.; Kulkarni, Ashwin (International Journal of Advances in Medicine, 2023)
Background: This survey aimed to investigate physicians’ perspectives on chronic constipation in patients with comorbidities, diagnosis and management of CC, and preferred laxatives used for treating CC in these patients. Methods: A 32-item, questionnaire-based online survey was conducted among 243 consulting physicians to gather information about CC with comorbidities, diagnosis and management strategies, and preferred laxatives. Results: The survey showed that 10%-39% of patients experienced CC for >3 months as reported by 61.7% of physicians, with diabetes being the most common comorbid condition. Patient noncompliance (93.8%) was identified as the main factor affecting management outcomes. The most preferred laxative by physicians in adult patients and the elderly was the combination of liquid paraffin+MOM+sodium picosulfate. The primary parameters considered by physicians when choosing a laxative were efficacy and tolerability. The laxative containing liquid paraffin + MOM + sodium picosulfate was reported to be effective for overnight relief by 44.9% of physicians in 60%-89% of patients. Physicians largely opined that side effects such as nausea/vomiting, abdominal cramps/pain, and anal seepage/ incontinence occurred in <1% of patients treated with liquid paraffin+MOM+sodium picosulfate. Conclusions: Clinical features aid in diagnosing CC and physicians prioritize treatment effectiveness when selecting laxatives. The participating physicians opined that combination laxatives consisting of liquid paraffin+MOM+sodium picosulfate are effective and well-tolerated for managing CC in patients with comorbidities. Hence, it is essential to consider their use for effective management of CC with comorbidities.